Effects of sepiolite addition to acrylic-latex paint on pull-off adhesion strength in nanosilver-impregnated and thermally-modified beech (Fagus orientalis L.) wood - Taghiyari, Hamid R.; Antov, Petar; Soltani, Abolfazl; Ilies, Dorina Camelia; Nadali, Elham; Lee, Seng Hua; Grama, Vasile; Simona, Tripa (Nature Research, 2024)
Sepiolite is a silicate mineral that improves the fire properties in solid wood when mixed with a water-based coating. The present study was carried out to investigate and evaluate the effects of sepiolite addition to acrylic-latex paint on the pull-off adhesion strength, as an important characteristic of paints and finishes used in the modern furniture industry and historical furniture as well for preservation and restoration of heritage objects. Sepiolite was added at the rate of 10, and brushed onto plain-sawn beech (Fagus orientalis L.) wood specimens, unimpregnated and impregnated with a 400 ppm silver nano-suspension, which were further thermally modified at 185 °C for 4 h. The results showed that thermal modification had a decreasing effect on the pull-off adhesion strength, primarily as a result of the thermal degradation of cell-wall polymers (mostly hemicelluloses). Still, a decreased wettability as a result of condensation and plasticization of lignin was also partially influential. Based on the obtained results,thermal modification was found to have a significant influence on pull-off adhesion strength. Sepiolite addition had a decreasing effectin all treatments, though the effect was not statistically significant in all treatments. The maximum and minimum decreases due to sepiolite addition were observed in the unimpregnated control (21) and the thermally-modified NS-impregnated (4) specimens. Other aspects of the sepiolite addition, and further studies that cover different types of paints and coatings, should be evaluated before coming to a final firm conclusion in this regard.